2018
DOI: 10.1371/journal.pone.0202468
|View full text |Cite|
|
Sign up to set email alerts
|

Implications of the Ebola virus disease outbreak in Guinea: Qualitative findings to inform future health and nutrition-related responses

Abstract: IntroductionDue to the close relationship between EVD and nutrition, the humanitarian community implemented various nutrition-specific and -sensitive interventions to stem the Ebola Virus Disease (EVD) outbreak in West Africa. Little, however, is known about stakeholder and community members’ perspectives toward this response in Guinea. Therefore, we aimed to firstly understand how EVD may have influenced the nutrition situation; and secondly to assess the perceived acceptability and effectiveness of the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 35 publications
0
53
0
1
Order By: Relevance
“…Similar studies had previously examined fewer aspects of lifestyle, such as social support, sleep pattern, and diet/nutrition. 16 , 17 , 18 , 19 , 20 , 30 To our knowledge, the present report is the first observational survey that examined a wide range of lifestyle changes during home self-isolation. The SMILE-C aligns with contemporary, official definitions of lifestyle as a multidimensional construct.…”
Section: Discussionmentioning
confidence: 91%
“…Similar studies had previously examined fewer aspects of lifestyle, such as social support, sleep pattern, and diet/nutrition. 16 , 17 , 18 , 19 , 20 , 30 To our knowledge, the present report is the first observational survey that examined a wide range of lifestyle changes during home self-isolation. The SMILE-C aligns with contemporary, official definitions of lifestyle as a multidimensional construct.…”
Section: Discussionmentioning
confidence: 91%
“…However, this was aimed for a minority of the caseload in ETUs and had a significant focus on the use of specialized products, generally used for the treatment of severe acute malnutrition [8]. Kodish et al interviewed key-informants to describe the acceptability and effectiveness of nutrition-specific response among community members and health professionals, but this was not related to care within ETUs itself [3].…”
Section: Discussionmentioning
confidence: 99%
“…Through key informant (KI) interviews, Kodish et al reviewed the use of three interim guidelines coissued by WHO in Guinea including the iGL. However, the findings were not specifically linked to this 2014 iGL [3]. A previous literature review found a limited number of publications on specific nutritional care in ETUs that often lacked detailed descriptions of the actual nutritional care provided (Ververs/Gabra to be submitted for publication).…”
Section: Introductionmentioning
confidence: 95%
“…This participatory study was designed as the final phase in a multi-phased, qualitative study conducted in Guinea and Sierra Leone. This phase had two primary objectives: (1) to provide a forum for presenting qualitative interview findings to stakeholders for their feedback and corroboration, and (2) to build consensus around priority areas that had been identified through previous qualitative work (Kodish et al , 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Findings from the NGT workshops were triangulated with semi-structured, qualitative interview data previously collected by the research team among organizational stakeholders and community members in both Guinea ( n = 27) and Sierra Leone ( n = 42). Those methods have been explained in detail elsewhere (Kodish et al , 2018).…”
Section: Methodsmentioning
confidence: 99%